Lady at her Toilette by Giulio Romano from Moscow Pushkin State Museum of Fine Arts as an Object of Social History of Art - Nazarova, Olga A. (Actual Problems of Theory and History of Art, 2019)
The so called Lady at her Toilette by Giulio Romano from the Moscow Pushkin State Museumof Fine Arts has been conventionally regarded as an imitation of famous Fornarina by Raphael. Social aspectof its origins have not been explored and its function has been defined only generally as a portrait or a depiction of “courtesan” or “mistress”, the issues of its possible patron and original context have not been assessed. Close examination of Lady at her Toilette’s distinct visual details dismisses the seeming similarities with frivolous female images known as belle and reveals strong affinities with painterly wedding epithalamia, which clearly indicates its own function as a wedding painting presenting Venus bestowing blessing upon a new bride. Having established the work’s function in general, the author has attempted to define a possible patron of this wedding epithalamia. Giulio Romano’s artistic career shows his involvement in the wedding of the Duke of Mantua Federico II Gonzaga and Margherita Paleologa, which took place in 1531. As a court painter Giulio was responsible for major decorative works in the city and created, among other, the bride’s portrait (Royal Collection, Hampton Court, London). This portrait turns out to be the closest analogy to the Moscow “Lady” in terms of composition, style, painterly manner and even the facial features of the women. This, along with other similarities, unequivocally indicates that they were created as a set — as a wedding set that includes the portrait of the young spouse and an allegorical depiction of Venus.
Keywords: Giulio Romano; social history of art; lady at her toilette; Renaissance wedding painting; wedding epithalamia